Perceived Mental Illness Stigma, Intimate Relationships, and Sexual Risk Behavior in Youth With Mental Illness. (May 2013) - Elkington, Katherine S.; Hackler, Dusty; Walsh, Tracy A.; Latack, Jessica A.; McKinnon, Karen; Borges, Cristiane; Wright, Eric R.; Wainberg, Milton L.
The current study examines the role of mental illness–related stigma on romantic or sexual relationships and sexual behavior among youth with mental illness (MI), including youths' experiences of stigma, the internalization of these experiences, and the behavior associated with managing stigma within romantic and sexual relationships. We conducted in-depth interviews with N = 20 youth with mental illness (MI) (55% male, 16-24 years, 75% Latino) from 4 psychiatric outpatient clinics in New York City. We conducted a thematic analysis to investigate shared experiences of MI stigma and its impact on youth's sexual or romantic relationships and associated behaviors. Our analysis revealed four main themes: (1) societal perceptions of those with MI as partners (societal stigma); (2) individual experiences of stigma within relationships (individual level); (3) internalized stigma of self as a partner (social-psychological processes); and (4) managing a stigmatized identity, of which some of the behaviors directly placed them at increased risk for HIV. We found that just under half of the sample ( n = 9/20) endorsed all themes, including engaging in HIV/STI sexual risk behaviors as a method to manage a stigmatized identity, which suggests that MI stigma and sexual risk may be linked. We discuss differences by gender and diagnosis. Findings provide new information for providers and researchers to address on the role of stigma experiences in the romantic and sexual behavior of youth in psychiatric treatment. Implications for stigma and HIV/STI prevention interventions are discussed.